2009
DOI: 10.1161/circulationaha.108.793208
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent Mesenchymal Stem Cells Acquire a Lymphendothelial Phenotype and Enhance Lymphatic Regeneration In Vivo

Abstract: Background-The importance and therapeutic value of stem cells in lymphangiogenesis are poorly understood. We evaluated the potential of human and murine mesenchymal stem cells (MSCs) to acquire a lymphatic phenotype in vitro and to enhance lymphatic regeneration in vivo. Methods and Results-We assessed the lymphendothelial differentiation of human and murine MSCs after induction with supernatant derived from human dermal microvascular endothelial cells, isolated lymphatic endothelial cells, and purified vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(97 citation statements)
references
References 40 publications
(36 reference statements)
2
95
0
Order By: Relevance
“…Although LECP were reported to derive from adipose [31], mesenchymal [30] or hematopoietic [59] stem cells, the majority of studies identified BM-produced myeloid-monocytic precursors as their main source [26]. Consistent with the monocytic origin, human LECP were successfully differentiated in vitro using monocytes from peripheral [27,32,33] or umbilical cord [24,54] blood and treatment with a VEGF-A/VEGF-C cocktail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although LECP were reported to derive from adipose [31], mesenchymal [30] or hematopoietic [59] stem cells, the majority of studies identified BM-produced myeloid-monocytic precursors as their main source [26]. Consistent with the monocytic origin, human LECP were successfully differentiated in vitro using monocytes from peripheral [27,32,33] or umbilical cord [24,54] blood and treatment with a VEGF-A/VEGF-C cocktail.…”
Section: Discussionmentioning
confidence: 99%
“…Such pro-lymphatic reprogramming has been shown for human monocytes isolated from peripheral or cord blood [24,27], human pluripotent stem cell lines [25], mouse embryonic cells [28], mouse BM-derived CD11b + and mononuclear cells [13,16,29], mouse and human mesenchymal stem cells [30] and adipose-derived stem cells [31]. The main criteria for defining differentiated cells as LECP are as follows: 1) expression of specific LEC markers [16,24,25,27]; 2) acquisition of an endothelial-specific cobblestone morphology and/or ability to form tubes when grown in matrigel [16]; 3) demonstrated function in vivo evidenced by integration into lymphatic vessels [12,15,22] and a statistically significant increase in lymphatic vessel density (LVD) in inflammatory and tissue remodeling models [24,25,32]; and 4) evidence for enhanced functionality of new lymphatics such as improved relief from lymphedema [32] and an accelerated rate of healing wounds [25].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to acquire a lymphatic phenotype in vitro and induce lymphatic regeneration in vivo [48], MSC can directly take part to vessel formation by transdifferentiation into endothelial cells and incorporation into the vessel wall [4], [49]. Furthermore, they can secrete several factors implicated in angiogenesis such as VEGF-A, angiopoietin-1 and bFGF [20], [50].…”
Section: Discussionmentioning
confidence: 99%
“…MSCs are able to express a lymphatic phenotype, when cultured in lymphatic induced medium and VEGF-C [115]. Vice versa, tumor cells secrete growth factors, cytokines, and chemokines to promote the migration and survival of MSCs [108].…”
Section: Extracellular Matrix (Ecm) With Cancer-associated Fibroblmentioning
confidence: 99%